2022
DOI: 10.1186/s40662-022-00306-1
|View full text |Cite
|
Sign up to set email alerts
|

Three-year follow-up of posterior chamber phakic intraocular lens with a central port design after deep anterior lamellar keratoplasty

Abstract: Background To evaluate clinical outcomes of the Visian implantable collamer lens (ICL) with a central port to correct myopia and astigmatism after deep anterior lamellar keratoplasty (DALK) for keratoconus throughout 3 years of follow-up. Methods This study included 20 eyes of 20 patients that underwent V4c ICL (13 eyes with a spherical ICL and 7 eyes with a toric ICL) implantation after DALK. Uncorrected (UDVA) and corrected (CDVA) distance visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Previous studies have demonstrated the safety and efficacy of these procedures after DALK. [24][25][26][27] On the other hand, when performing a triple procedure, we suggest using a capsular tension ring to facilitate the exchange of the lens in case of an unexpected refractive result or a change in the donor button.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the safety and efficacy of these procedures after DALK. [24][25][26][27] On the other hand, when performing a triple procedure, we suggest using a capsular tension ring to facilitate the exchange of the lens in case of an unexpected refractive result or a change in the donor button.…”
Section: Discussionmentioning
confidence: 99%
“…The Visian Implantable Collamer Lens (Staar Surgical AG, Nidau, Switzerland), with a central port design (V4c) and a posterior chamber phakic intraocular lens (IOL) has been extensively utilized for high myopia correction since its commercial availability in 2011. Compared to prior ICL models, the V4c model has exhibited a substantial reduction in reported complications due to enhanced aqueous humor flow and preserved anterior segment physiology [4][5][6]. However, limited research exists on the impact of the V4c model on retinal and choroidal morphology, which are vital for maintaining patients' visual function [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%